Inhibition effect of N,N-diglycidyl-4-glycidyloxy aniline on photosensitized cationic polymerization of formulations involving resorcinol diglycidyl ether and poly(propylene glycol)diglycidyl ether - Harikrishna, Reghunathan (Journal of Photochemistry and Photobiology A-Chemistry, 2015)
Cationic photopolymerization studies of poly(propylene glycol)diglycidyl ether with and without 25 wt% of resorcinol diglycidyl ether were carried out in presence of bis(4-methylphenyl)iodonium hexafluorophosphate as photoinitiator. Analyses were carried out using polychromatic radiation at different temperatures in a photo differential scanning calorimeter. The formulations showed an enhancement in the rate of polymerization on addition of resorcinol diglycidyl ether. The same formulations when subjected to photosensitized polymerization in presence of 1-chloro-4-propoxy-9H-thioxanthen-9-one, showed a reverse behavior in rate due to partial absorption of radiation by resorcinol diglycidyl ether. Studies carried out on by the addition of N,N-diglycidy1-4-glycidyloxy aniline as inhibitor on the photosensitized formulations showed higher scavenging activity by inhibitor. The addition of nitrogen containing epoxy monomer as inhibitor can lead to its possible crosslinking within the matrix on polymerization along with a decrease in rate of polymerization without compromising on the final observed conversion. This effect can occur readily for non vitrifying systems. Thus, this observation provides an insight into its possible usage in a rate controlled photopolymerizable epoxy formulations. The photopolymerization kinetics were found to depend on the nature of generation, propagation and scavenging of active centers which are heavily dependent on diffusional restrictions imparted by in situ viscosity of the system. The kinetic estimations as well as evaluation of autocatalytic kinetic model are investigated. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Glycidyl ether; Inhibition; kinetic model; kinetics; Photopolymerization; Photosensitization